Study on the machining of Al–SiC functionally graded metal matrix composite using die-sinking EDM. (2nd January 2019) - Uthayakumar, M.; Babu, K. Vinoth; Kumaran, S. Thirumalai; Kumar, S. Suresh; Jappes, J. T. Winowlin; Rajan, T. P. D.
ABSTRACT: Functionally graded aluminum matrix composites (FGAMCs) are new materials with excellent capabilities for design and development of complex engineering works. In this work, FGAMCs are machined using electrical discharge machining (EDM) with the process input parameters such as pulse current, pulse on time, and zone position in brake disk. Design of experiments is used for the experimental planning with full factorial method. The selected input process parameters are optimized using gray relational analysis to minimize the electrode wear ratio, overcut, power consumption, and surface roughness. The influential studies of input process parameters on the output responses are also conducted. The optimal EDM parameter setting for achieving better output parameters is pulse current at 5 A, pulse on time at 50 µs and 45 mm zone position distance in the brake disk. The pulse current (39.40%) contributed the maximum in minimizing the output responses. Further, the surface morphology is also analyzed on the material to observe the crater formation and the erosion mechanism.